Isolation and structural characterization of a non-diketopiperazine phytotoxin from a potato pathogenic Streptomyces strain. Issue 20 (18th October 2019) - Lapaz, María Inés; López, Andrés; Huguet-Tapia, José Carlos; Pérez-Baldassari, Martín Fabián; Iglesias, Cesar; Loria, Rosemary; Moyna, Guillermo; Pianzzola, María Julia
Abstract: Two Streptomyces spp. strains responsible for potato common scab infections in Uruguay which do not produce diketopiperazines were identified through whole-genome sequencing, and the virulence factor produced by one of them was isolated and characterized. Phylogenetic analysis showed that both pathogenic strains can be identified as S. niveiscabiei, and the structure of the phytotoxin was elucidated as that of the polyketide desmethylmensacarcin using MS and NMR methods. The metabolite is produced in yields of ∼200 mg/L of culture media, induces deep necrotic lesions on potato tubers, stuns root and shoot growth in radish seedlings, and is comparatively more aggressive than thaxtomin A. This is the first time that desmethylmensacarcin, a member of a class of compounds known for their antitumor and antibiotic activity, is associated with phytotoxicity. More importantly, it represents the discovery of a new virulence factor related to potato common scab, an economically-important disease affecting potato production worldwide. Graphical Abstract: